Molecular pathogenesis of secondary bacterial infection associated to viral infections including SARS-CoV-2 - Sounik Manna; Piyush Baindara; Santi M. Mandal (Elsevier, 2020)
Secondary bacterial infections are commonly associated with prior or concomitant respiratory viral infections. Viral infections damage respiratory airways and simultaneously defects both innate and acquired immune response that provides a favorable environment for bacterial growth, adherence, and facilitates invasion into healthy sites of the respiratory tract. Understanding the molecular mechanism of viral-induced secondary bacterial infections will provide us a chance to develop novel and effective therapeutic approaches for disease prevention. The present study describes details about the secondary bacterial infection during viral infections and their immunological changes.The outcome of discussion avails an opportunity to understand possible secondary bacterial infections associated with novel SARS-CoV-2, presently causing pandemic outbreak COVID-19.